ANALISIS VALENSI BUKU EINFAH DEUTSCH - PUJI RAHARJO, HUDA (LATERNE, 2016)
Learning german in senior high school in line with the theory saville-troike said that a foreign language used for the needs of education. In learning the language of germans lks worn is a book einfach deutsch. Relating to the use of verbs in book einfach deutsch in senior high school and vocationa high schooll never peeling good behavior from syntactic and semantic. The purpose of this research is described behavior syntactic and semantis from verben in the german language which have benefits for teachers and students in ease learning german at school . Verb is the most important components in a sentence. The research is deskriptif-kualitatif research that focus against the implementation of the theory valence on german verb in the senior high school level. To classify verba-verba in this book , the researchers applied the theory valence of which made it possible to analyze the data and good syntactic semantic. The result, verba-verba who was classified arranged alphabetically be glosar books einfach deutsch for students could be beneficial in supporting learning german at school. Keywords : Valenz, Deutsch, Verbvalenz.